Sugarcane powder biofortified with kefir grains: effect of spray drying process (2018)
ABSTRACT: The Spray Drying process of sugarcane concentrate fermented with Kefir Grains was evaluated using Response Surface Methodology based on the following independent variables: Air Inlet Temperature (AIT) (120-140ºC), Air Outlet Temperature (AOT) (65-75°C), and Atomizing Disk Speed (ADS) (20000-25000 rpm). Results were analyzed using the Design Expert 8.0.5.2 software, and the following conditions were found to be optimal: AIT 125ºC, AOT 65ºC, and ADS 25000 rpm. Likewise, optimal values for dependent variables were: moisture = 3.4±0.6%, aw = 0.210±0.030, solubility = 97.54±0.01%, fractal dimension = 2.64±0.04, particle sizes (D(3,2) = 14.78 μm and D(4,3) = 35.9 μm), yield = 81.5±8.3%, and lactobacilli, lactococci and yeast survival = 85.4, 67.1 and 74.9%, respectively. Results showed that, at optimal conditions for spray drying, the process has a good yield and produces a stable powder food with good levels of microorganisms from KG. It is also very soluble in aqueous phases, which facilitates its use as a reconstituted beverage or as an ingredient in several industries.